Elevation of BUN is predictive of long-term mortality in critically ill patients independent of 'normal' creatinine - Beier, Kevin (2011)
OBJECTIVE: We hypothesized that elevated BUN can be associated with all cause mortality independent of creatinine in a heterogeneous critically ill population. DESIGN: Multicenter observational study of patients treated in medical and surgical intensive care units. SETTING: 20 intensive care units in two teaching hospitals in Boston, Massachusetts PATIENTS: 26,288 patients, age ≥ 18 years, hospitalized between 1997 and 2007 with creatinine 0.80–1.30 mg/dl. MEASUREMENTS: BUN at ICU admission was categorized as 10–20, 20–40 and >40 mg/dl. Logistic regression examined death at days 30, 90 and 365 post-ICU admission as well as in hospital mortality. Adjusted odds ratios were estimated by multivariable logistic regression models. INTERVENTIONS: None KEY RESULTS: BUN at ICU admission is predictive for short term and long term mortality independent of creatinine. 30 days following ICU admission, patients with BUN >40 mg/dl have an Odds Ratio for mortality of 5.12 (95% CI, 4.30–6.09; P<.0001) relative to patients with BUN 10–20 mg/dl. BUN remains a significant predictor of mortality at 30 days following ICU admission following multivariable adjustment for confounders, patients with BUN >40 mg/dl have an Odds Ratio for mortality of 2.78 (95% CI, 2.27–3.39; P<.0001) relative to patients with BUN 10–20 mg/dl. 30 days following ICU admission, patients with BUN 20–40 mg/dl have an OR of 2.15 (95% CI, 1.98–2.33; <.0001) and a multivariable OR of 1.53 (95% CI, 1.40–1.68; P<.0001) relative to patients with BUN 10–20 mg/dl. Results were similar at 90 and 365 days following ICU admission as well as in-hospital mortality. A subanalysis of patients with blood cultures (n= 7,482), demonstrated that BUN at ICU admission was associated with the risk of blood culture positivity. CONCLUSION: Among critically ill patients with Cr 0.8–1.3 mg/dl, an elevated BUN is associated with increased mortality, independent of serum creatinine.